RESPONSE OF SOIL AND FOLIAR APPLICATION OF SILICON AND MICRO NUTRIENTS ON SOIL NUTRIENT AVAILABILITY OF SAPOTA - K. A. LALITHYA; H. P. BHAGYA; TAJ, AMREEN; K. BHARATI; HIPPARAGI , KULAPATI (The Bioscan, 2013)
The silicon sources like potassium silicate and calcium silicate and Solubor as boron source and kiecite –G as micronutrient source were used for the field experiment to know the response of soil and foliar application of silicon and micronutrients which influences on nutrient availability. With application of potassium silicate at 8 mL per litre resulted in lowest organic content (1.34 %) and treatment control showed the highest organic carbon content (1.68 %) in the soil at fruit harvest stage. 145.33 kg/ha, 9.68 kg/ha and 105.63 kg/ha of available nitrogen, phosphorous and potassium content were observed respectively in the treatment with application of potassium silicate at 8 mL per litre as foliar spray where as more nutrient contents were observed in the soils of control plots at the time of fruit harvest. This indicates that at the time of fruit harvest minimum nutrients were available in the soil and maximum uptake of nutrients were observed in the silicon treated plot resulted in maximum production and quality of fruits.